How Geo-Virtual Volcanism Exploration Scaffolds Spatial Thinking in Secondary Geography Students? - Muhammad Happy Nugroho (CV Bumi Spasial, 2026)
This research examines Geo-Virtual Volcanism Exploration (GVVE), a Spatial IO-based Virtual Learning Environment (VLE), in facilitating advanced spatial thinking for complex lithospheric processes. While general VLEs exist in geography education, no study has deployed a web-based 3D VLE, structured around Jo & Bednarz’s spatial taxonomy, for lithospheric volcanism within an Indonesian secondary context. Furthermore, existing Spatial-TPACK frameworks lack empirical testing through situated, open-access platforms anchored to a local case study (Mount Kelud). Adopting an ADDIE-structured R&D framework, GVVE integrated TPACK principles and underwent validation before field implementation with educators and students (n=31). Testing substantiated high efficacy, yielding feasibility scores of 91.1% (teachers) and 86.6% (students). Analysis indicates a substantive qualitative progression in spatial cognition, transitioning students from elementary recognition to complex transformation. Participants achieved an 87.5% success rate in autonomous 3D spatial analysis of volcanic phenomena, outcomes previously unattainable through two-dimensional, static instructional media. Theoretically, findings demonstrate GVVE operationalizes the Jo and Bednarz Taxonomy by providing cognitive scaffolds for volumetric spatial reasoning. Practically, by fostering deep analytical capabilities without specialized hardware, this immersive approach serves as a transformative catalyst for elevating spatial literacy in contemporary geography education.